Covariates of non-dipping and elevated night-time blood pressure in ischemic stroke patients: the Norwegian Stroke in the Young Study*. (3rd July 2016) - Saeed, Sahrai; Waje-Andreassen, Ulrike; Lønnebakken, MT; Fromm, Annette; Øygarden, Halvor; Naess, Halvor; Gerdts, Eva
Abstract: Abnormal night-time blood pressure (BP) reduction is associated with increased cardiovascular risk in hypertension. Little is known about the prevalence and covariates of night-time BP reduction in ischemic stroke patients. Clinic and ambulatory BP measurements were recorded in 268 stroke survivors aged 15–60 years. The degree of night-time dipping was calculated from the difference between day-time and night-time mean BP, and defined as non-dipping if < 10%. Aortic stiffness was derived from carotid–femoral pulse-wave velocity (PWV) by applanation tonometry and carotid intima–media thickness (cIMT) by ultrasound. A non-dipping pattern was found in 38%. Non-dippers had higher PWV, mean cIMT and night-time BP, and included more patients with history of hypertension, diabetes and high for age PWV compared to dippers (all p  < 0.05). In multivariate logistic regression analyses, non-dipping was associated with high for age PWV [odds ratio (OR) = 2.28; 95% confidence interval (CI) 1.06–4.92, p  < 0.05] independent of history of hypertension and other confounders, while elevated night-time BP was associated with increased cIMT (OR = 3.83; 95% CI 1.01–14.50, p  < 0.05) independent of non-dipping status, male gender, obesity, antihypertensive treatment and high for age PWV. In conclusion, in the Norwegian Stroke in the Young Study, non-dipping BP pattern was common and associated with increased aortic stiffness.